IMPLEMENTASI METODE FORWARD CHAINING UNTUK MENDIAKNOSA PENYAKIT AYAM PETELUR BERBASIS ANDROID - Reni Veliyanti; Dani Sasmoko (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
Current technological advances and the challenges faced are increasingly diverse, therefore the use of android technology with the forward chaining method can be done in the disease identification process in laying hens. This is to prevent the spread of the disease by early identification of sick chickens. This system transfers the ability of experts in identifying diseases of laying hens and diagnosing their pain and providing treatment solutions. This system helps farmers at Yuli Farm to increase the productivity of laying hens.